Understanding Heart Disease - Selzer, Arthur (University of California Press, 2022)
Diseases of the heart are the leading cause of death in the Western world. Health professionals and the general public alike eagerly watch advances in the prevention, diagnosis, and treatment of heart disease. Yet the more spectacular aspects of medical progress in the field are often reported prematurely and their potential benefits exaggerated. Written in clear, accessible language, this book presents an authoritative and balanced.
Keywords: Heart -- Diseases -- Popular works.; Heart -- Diseases.; Heart Diseases; Cœur -- Maladies -- Ouvrages de vulgarisation.; Cœur -- Maladies.; Heart -- Diseases; Popular works